Testosterone in advance age: a New Zealand longitudinal cohort study: Life and Living in Advanced Age (Te Puāwaitanga o Ngā Tapuwae Kia Ora Tonu). Issue 11 (12th November 2017) - Connolly, Martin J; Kerse, Ngaire; Wilkinson, Tim; Menzies, Oliver; Rolleston, Anna; Chong, Yih Harng; Broad, Joanna B; Moyes, Simon A; Jatrana, Santosh; Teh, Ruth
Abstract : Objectives: Serum testosterone (T) levels in men decline with age. Low T levels are associated with sarcopenia and frailty in men aged > 80 years. T levels have not previously been directly associated with disability in older men. We explored associations between T levels, frailty and disability in a cohort of octogenarian men. Setting: Data from all men from Life and Living in Advanced Age Cohort Study in New Zealand, a longitudinal cohort study in community-dwelling older adults. Participants: Community-dwelling (> 80 years) adult men excluding those receiving T treatment or with prostatic carcinoma. Outcomes measures: Associations between baseline total testosterone (TT) and calculated free testosterone (fT), frailty (Fried scale) and disability (Nottingham Extended Activities of Daily Living scale (NEADL)) (baseline and 24 months) were examined using multivariate regression and Wald's χ 2 techniques. Subjects with the lowest quartile of baseline TT and fT values were compared with those in the upper three quartiles. Results: Participants: 243 men, mean (SD) age 83.7 (2.0) years. Mean (SD) TT=17.6 (6.8) nmol/L and fT=225.3 (85.4) pmol/L. On multivariate analyses, lower TT levels were associated with frailty: β=0.41, p=0.017, coefficient of determination (R 2 )=0.10 and disability (NEADL) (β=−1.27, p=0.017, R 2 =0.11), low haemoglobin (β=−7.38, p=0.0016, R 2 =0.05), high fasting glucose (β=0.38, p=0.038, R 2 =0.04) and high C reactive protein (CRP) (β=3.57, p=0.01, R 2 =0.06). Low fT levels were associated with frailty (β=0.39, p=0.024, R 2 =0.09) but not baseline NEADL (β=−1.29, p=0.09, R 2 =0.09). Low fT was associated with low haemoglobin (β=−7.83, p=0.0008, R 2 =0.05) and high CRP (β=2.86, p=0.04, R 2 =0.05). Relationships between baseline TT and fT, and 24-month outcomes of disability and frailty were not significant. Conclusions: In men over 80 years, we confirm an association between T levels and baseline frailty scores. The new finding of association between T levels and disability is potentially relevant to debates on T supplementation in older men, though, as associations were not present at 24 months, further work is needed.